2023
DOI: 10.1007/s10648-023-09750-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Benefits of Attending Forest School for Preschool Children: a Systematic Review

Abstract: Forest school is a form of outdoor learning that takes children into regular and repeated learning experiences in natural settings. Being based on a comprehensive experience with nature, it is assumed to be beneficial for learning and to promote restorative effects on cognitive and emotional function in preschool children. This review aimed to examine the available evidence on the benefits of forest school compared to indoor school activities in children aged 3 to 6 years. We searched for studies on forest sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Taken together, these studies represent the growing body of evidence to support delivery of Forest School in a range of settings and with diverse populations, which has been reflected by the growing number of systematic reviews on the topic (Dabaja, 2022a(Dabaja, , 2022bGarden & Downes, 2023a;Harris, 2022;Sella et al, 2023). These studies tend to speak to the benefits of Forest School for participants.…”
Section: Understanding the E Xisting E Vidence Basementioning
confidence: 93%
See 2 more Smart Citations
“…Taken together, these studies represent the growing body of evidence to support delivery of Forest School in a range of settings and with diverse populations, which has been reflected by the growing number of systematic reviews on the topic (Dabaja, 2022a(Dabaja, , 2022bGarden & Downes, 2023a;Harris, 2022;Sella et al, 2023). These studies tend to speak to the benefits of Forest School for participants.…”
Section: Understanding the E Xisting E Vidence Basementioning
confidence: 93%
“…The focus of much research relating to Forest School has been an examination of the benefits to participants (Knight, 2011a, 2011b, 2011c), and this has been demonstrated through a number of recent systematic reviews (see Dabaja, 2022a, 2022b; Garden & Downes, 2023a; Harris, 2022; Sella et al., 2023).…”
Section: Understanding the Existing Evidence Basementioning
confidence: 99%
See 1 more Smart Citation
“…With these rules in mind, caregivers and teachers could teach children from an early age onward to be aware of their personal psychological resources and to strengthen them. Learning to enjoy food through sufficient time for meals and teachers as role models [126] and regular walks in forests and parks with a mindful sensory experience of flora and fauna [127], for example, can be organized in nearly every preschool, kindergarten, or school alongside explaining the basics of ecologically sustainable behavior [128,129]. Forest schools provide an opportunity to teach primary and secondary school students not only about the climate crisis and ecologically sustainable behavior but also to instill solidarity and social responsibility in them [130].…”
Section: Implications For Practicementioning
confidence: 99%
“…Particularly, previous literature suggested that being involved in structured motor intervention activities may bring benefits, especially for the development of the motor and cognitive domain (e.g., gross motor abilities, locomotor skills; [ 7 , 49 ]). Finally, it is well-established that outdoor educational activities bring benefits to children’s development [ 6 , 9 ]. Based on this empirical foundation, structured motor activities conducted outdoors, in green space, in a group of nursery children should be much more beneficial for the development of cognitive and socio-emotional competencies.…”
Section: Introductionmentioning
confidence: 99%